Taboo Words In The Lyrics Of Cardi B On Album Invasion Of Privacy - putri yanelia; alfian alfian; adang ridwan (English Language, Linguistics, Literature, And Education Journal, 2020)
This research analyzes taboo words in the Album Invasion of Privacy entitled Taboo words in the lyrics of Cardi b on Album Invasion of Privacy. The purpose of this study to describe the types, functions and meanings of the words taboo in Album Invasion of Privacy by Cardi b and the object in this study is Album Invasion of Privacy. This research uses descriptive qualitative research and the object of this research is Album Invasion of Privacy. The data from this study are all taboo words that the writer found in the Album Invasion of Privacy. The data is classified from taboo words according to Battistella theory, taboo word functions using Wardhaugh's theory, and taboo meanings categorized using Geoffrey's theory. Furthermore, the results showed that there are four types of taboo words, consisting of; obscenity, epithets, vulgarity, profanity and also the writer found that vulgarity data is more dominantly used in song lyrics in the Album Invasion of Privacy. Furthermore, the function of the taboo words consists of drawing attention to oneself, show contempt, to be provocative, to mock authority and the writer found that to contempt is more dominantly used in song lyrics in the Album Invasion of Privacy. Finally, there are two taboo meanings found, conceptual, connotative and conceptual data which is more dominantly used in Album Invasion of Privacy.